1998
DOI: 10.1159/000030274
|View full text |Cite
|
Sign up to set email alerts
|

Selective Interactions between Prostate Fibroblast and Epithelial Cells in Co-Culture Maintain the BPH Phenotype

Abstract: Paracrine interactions between primary cultured prostate epithelial cells and stromal fibroblasts were investigated in relation to morphology, growth, androgen sensitivity and secretory activities using co-cultures in which the two populations were separated by a microporous membrane. In this new model system, both cell types maintained several aspects of the differentiated phenotype including the capacity to express 5α-reductase iso-enzymes and androgen receptors, to respond to androgens and to secrete prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Efforts to model stromal and epithelial cell interactions in in vitro culture have helped elucidate the cross talk between cell types (Bayne et al 1998, Habib et al 2000. In vitro coculture studies have produced conflicting results of cell regulation.…”
Section: Cell Culture Models To Understand Ar Function and Cell Commumentioning
confidence: 99%
“…Efforts to model stromal and epithelial cell interactions in in vitro culture have helped elucidate the cross talk between cell types (Bayne et al 1998, Habib et al 2000. In vitro coculture studies have produced conflicting results of cell regulation.…”
Section: Cell Culture Models To Understand Ar Function and Cell Commumentioning
confidence: 99%
“…The addition of conditioned medium from stromal cell cultures and the presence of testosterone or dihydrotestosterone facilitates morphogenesis and the formation of luminal structures in Matrigel, the outer cells expressing high-molecular-weight cytokeratins (K1, 5, 10, and 14) and the inner cells expressing K18 (Lang et al 2001). Despite proper three-dimensional arrangement, expression of AR does not regenerate the entire transcriptional program and the in vivo response of androgen stimulation (Bayne et al 1998;Hudson et al 2000). Secretory differentiation and androgen responsiveness are only reliably achieved when human PECs are recombined with rat urogenital mesenchyme and implanted beneath the renal capsule of athymic mice (Hayward et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to overcome this limitation, we chose a co-culture system of epithelial cells and fibroblasts from benign hyperplastic prostate tissues, employing a defined medium. A morphological study (8) on cells from BPH tissues demonstrated that when grown in co-culture, the epithelial cells exhibited round nuclei, tonofibrils, and microvilli, and the fibroblasts had elongated nuclei, large amounts of Golgi apparatus, and cilia; these are characteristics of the differentiated state. However, there were no studies using a co-culture model to examine differential gene expression in cells derived from BPH tissues.…”
Section: Discussionmentioning
confidence: 99%